Tobacco use among the elderly: a systematic review and meta-analysis Uso de tabaco entre idosos: revisão sistemática e meta-análise - Valeska Marinho; Jerson Laks; Evandro Silva Freire Coutinho; Sergio Luís Blay (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to combine the results of identified surveys on the prevalence of tobacco use in old age to estimate world prevalence of tobacco use and possible factors related to such behavior among the elderly. The literature search included electronic databases such as MEDLINE, LILACS, and Biological Abstracts, hand-searching of specialist journals and cited reference searches. The combined global prevalence was estimated using the random effects model. The total number of elderly subjects included in all surveys was 140,058, with data available from all the continents. Overall prevalence of tobacco use was 13% in both genders (22% male and 8% female). The prevalence rates were heterogeneous among surveys and were associated with smoking definition, questionnaire application, and country economic status. Few epidemiological studies assessed tobacco use among the elderly. A higher prevalence rate of tobacco use in males who live in higher income countries could be found, although additional evidence regarding elderly samples is still required. O objetivo deste estudo foi combinar os resultados de pesquisas identificadas sobre a prevalência do tabagismo em idosos, para estimar sua prevalência mundial e possíveis fatores relacionados a este tipo de comportamento entre eles. A revisão da literatura incluiu busca nas bases de dados eletrônicas como MEDLINE, LILACS e Biological Abstracts, busca manual em jornais especializados e nas referências citadas. A prevalência global combinada foi estimada usando-se o modelo de efeitos randômicos. O número total de idosos incluídos em todos os levantamentos foi 140.058, com dados disponíveis em todos os continentes. A prevalência de tabagismo foi de 13% em ambos os sexos (22% homens e 8% mulheres). As taxas de prevalência foram heterogêneas e estiveram associadas com a definição de tabagismo, aplicação do questionário e com a economia de cada país. A maior taxa de prevalência foi encontrada entre idosos do sexo masculino que vivem em países de renda mais alta.